Limbah Penebangan Kayu di Perusahaan PT. Dwimajaya Utama - I Nyoman Surasana; Kristiani D Limbong; Yosep (Journal of Environment and Management, 2020)
This study aims to determine the volume of wood waste (in units of m3 and %) in IUPHHK-HA PT. Dwimajaya Utama. The research was carried out in cutting plots K-18 (RKT 2015) and felling plots J-21 (RKT 2016). As many as 8 units of sample plots measuring of 100 m x 100 m were purposively selected and then the waste resulted from 56 trees that had been felled were observed. The results showed that the woods potential on the cutting plot K-18 were 229.32 m3 while on plot J-21 were 200.03 m3, total volume of waste from the two cutting plots were 429.35 m3. Second, the reali-zation of logs production on the felling plot K-18 were 165.29 m3 (72.07%) and on plot J-21 were 145.73 m3 (72.86%) and the total from the two cutting plots were 311.02 m3 (72.44%). Thirdly, the mount of felling waste on felling plot K-18 were 64.05 m3 (27.93%) and on plot J-21 were 54.28 m3 (27.14%); resulting the total waste from both felling plots were 118.33 m3 ( 27.56%). Percentage of waste to production on felling plot K-18 were 38.75%, and on plot J-21 were 37.25%, and the mean from the two cutting plots were 38.00%. Forest potential structure for the two logging plots, namely timber potential around 429.35 m3, realized logs production of 311.02 m3 (72.44%) and resulted waste around 118.33 m3 (27.56%). The relatively low percentage of felling waste indicates that the application of RIL (Reduce Impact Logging) in logging activities is relatively successful.